Assessment as Learning in Islamic Religious Education: A Literature Review of Its Implementation in Elementary Schools - Lutfiah Holifa Balkis; Abdul Munip (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This study examines the implementation of assessment as learning in Islamic Religious Education (PAI) at the elementary school level through a systematic literature review. The problem addressed in this research is the dominance of traditional, cognitively oriented assessment practices that limit students’ engagement and the internalization of Islamic values. This study aims to analyze the conceptual framework, implementation strategies, and challenges of assessment as learning in PAI. The method employed is a systematic literature review (SLR) of 18 scholarly articles published between 2015 and 2025, collected from academic databases using specific keywords and analyzed through content analysis. The findings reveal that although there has been a shift toward authentic and holistic assessment approaches, the implementation of assessment as learning remains limited and not yet systematically integrated into classroom practices. Reflective strategies such as self-assessment, peer assessment, and learning journals are identified but are applied inconsistently and depend largely on teacher initiative. The study also finds that assessment as learning has significant potential to enhance students’ metacognitive awareness, learning responsibility, and internalization of Islamic values. However, its implementation is hindered by challenges such as limited teacher understanding, lack of training, time constraints, and the absence of practical assessment instruments. Overall, this study highlights a gap between theoretical developments and practical application, emphasizing the need for more systematic and context-based assessment models in Islamic education.